Thermal and Oxidation Response of UHTC Leading Edge Samples Exposed to Simulated Hypersonic Flight Conditions. Issue 3 (12th February 2013) - Parthasarathy, Triplicane A.; Petry, Melvin D.; Cinibulk, Michael K; Mathur, Tarun; Gruber, Mark R.; Smialek, J.
<x xml:space="preserve">Abstract</x> Sharp leading edge (LE) samples of UHTC (20 vol%SiC–HfB2) and SiC were exposed to simulated hypersonic flight conditions using a direct‐connect scramjet rig and their thermal and oxidation responses measured. The measured back‐wall temperatures and scale thicknesses were significantly smaller than might be expected from stagnation temperatures at the LE. Furthermore, the scale that formed around the LE was more uniform than expected from the steep drop in cold wall heat flux with distance from the tip. These results were interpreted and rationalized using physics‐based models. An aerothermal model in combination with an oxidation model accounted for the observed scale thicknesses at the tip and their slight variation with distance. The scale thicknesses were similar to values reported for exposures in furnaces at temperatures calculated for the tip, but less than those reported in arc jet tests. The formation of hafnon (HfSiO4) and the absence of external glassy layer and of silica in the outer portions of the oxide region are unique to scramjet tested samples, presumably due to the high fluid flow (high shear and evaporation) rates.